Economic activities, illness pattern and utilisation of health care facilities in the rural population of KwaZulu-Natal, South Africa - Monjurul Hoque (AOSIS, 2009)
Background: The study was undertaken among the rural and black communities of the Uthungulu health district of the KwaZulu-Natal province, South Africa. Method: A cross-sectional community-based descriptive study was conducted. A multi-stage sampling strategy was adopted to obtain a representative sample of the communities. Results: The mean age of the population was 27 years and majority was female (54%). Among the adult population only 30% were educated, 19% were engaged in some form of economic activities while 9% were in the formal employment sector. The average monthly income per household was R1 301 (95% CI, R1 283; R1 308). The illnesses were reported by 27% of the total population over a period of one month. Notably higher rates of female individuals (29%) were sick compared to males (24%, p < 0.001). The rates of illnesses among adult females (39%) were also significantly higher than among males (31%, p < 0.009). Most of them (69%) attended primary health care (PHC) clinics for medical services, while 67% reported chronic conditions. Age (OR = 1.4), gender (OR = 0.711), education (OR = 0.64) and economic activities (OR = 1.9) were found to be associated with being ill or not. Conclusion: The rural black communities are underdeveloped and deprived, which results in higher prevalence of illnesses; however, the utilisation of PHC facilities is comparatively higher than in the rest of the province and other parts of the country. Interventions to improve community health care services among the deprived population should be focused through public health strategies such as all-encompassing PHC that includes health promotion, education and basic essential amenities.